Association between cardiovascular disease- and inflammation-related serum biomarkers and poor lung function in elderly - Egervall, K. ; 0000-0003-2920-9548; Rosso, A. ; 0000-0001-6603-2855; Elmståhl, S. (Clinical Proteomics, 2021)
Background: Cardiovascular disease (CVD) is a common comorbidity in chronic obstructive pulmonary disease (COPD) and reduced lung function is an important risk factor for CVD and CVD-related death. However, the mechanisms behind the increased risk for CVD in COPD patients are not fully understood. Methods: We examined the association between CVD- and inflammation-related serum biomarkers, and pulmonary function in a geriatric population. 266 biomarkers related to CVD and inflammation were analyzed in blood samples from 611 subjects aged 66–86 years who participated in the Good Aging in Skåne study. Serum levels were assessed by a proximity extension assay. Pulmonary function was measured using the lower limit of normality (LLN) spirometry criteria, i.e., forced expiratory volume in 1 s (FEV1)/forced vital capacity (FVC) < LLN. Logistic regression models were implemented and multiple comparisons were accounted for. Results: 10.3% of the study participants fulfilled pulmonary function decline criteria according to LLN. Out of the 266 biomarkers, only plasminogen activator, urokinase receptor (PLAUR) was statistically significantly associated with decreased pulmonary function. We could not find a statistically significant association between pulmonary function decline and other biomarkers previously linked to COPD, such as interleukin 6, tumor necrosis factor and surfactant protein D. Conclusion: We found that serum levels of PLAUR are associated with pulmonary function decline in older adults. PLAUR is activated following inflammation and promotes matrix metallopeptidase (MMP) activation and extracellular matrix (ECM) degradation. This implies that PLAUR could play a role in the early phase of COPD pathogenesis.
Publisher Copyright: © 2021, The Author(s).
Keywords: Cardiovascular disease; Inflammation; Lung function decline; Proteomics